Arbitraje comercial internacional y tutela cautelar: colaboración entre jueces y árbitros en la adopción y reconocimiento de medidas cautelares internacionales - Sueiro Varhen, Víctor Rogelio (2020)
When referring to international commercial arbitration in Peru, two questions that have received little doctrinary reflection arise. These are, on one hand, the possibility that a Peruvian court may adopt a precautionary measure in assistance of a commercial arbitration based abroad and, on the other hand, the possibility of recognition by the Peruvian courts of a precautionary measure issued in the context of a commercial arbitration based abroad. They constitute the two sides of the same legal problem to which the author aims to reply by proposing a solution through a solid argumentative development. In this article, the author’s analysis departs from the importance of the right to effective international judicial protection, emphasizing on international precautionary protection. Moreover, he reflects on the duty of cooperation of the state courts in order to safeguard the effectiveness of precautionary protection in international commercial arbitration. At last, the author proposes certain criteria or parameters that would come in useful for the Peruvian state courts in order to adopt and recognize precautionary measures in support of international commercial arbitration when based abroad.